Developing an Acceptance Model for Use with Online Video-Sharing Platforms - Ittipat Chinangkulpiwat; Singha Chaveesuk; Wornchanok Chaiyasoonthorn (My University, 2021)
Online video-sharing platforms have increased their popularity significantly in recent years. For example, YouTube has grown rapidly and become the most visited website in the world. Video-sharing platforms work by allowing users to provide content, view, subscribe, like, dislike and comment on the platform. They provide cost-saving, remote access, improved learning, stress relief, and available advantages 24 hours per day. This paper aimed to develop a conceptual framework to comprehend the acceptance to use video-sharing platforms and proposed a conceptual framework developed from a prior conceptual framework of UTAUT and IS Success model. A structural equation model was applied utilizing confirmatory factor analysis to validate the acceptance model towards an acceptance model for other technological platforms.
Keywords: Technology Adoption and User Behaviour; Digital Marketing and Social Media; Customer Service Quality and Loyalty